(untitled) (Journal of Advanced Research in Social Sciences, 2020)
This cross sectional study was carried out to assess the prevalence and factors affecting sexual harassment (SH) among female staffs of a supermarket in Kathmandu, Nepal. The data were collected with self-administered questionnaire from 170 staffs. Uni-variate (descriptive detail) and bivariate (statistical detail) analyses were the methods applied. Among 24.1% of sexually harassed respondents, the most common was 15-30 years’ age group. Moreover, 80.5% of the victims were harassed verbally, 39% non-verbally and 48.8% physically. The harassment occurred either when they were alone (non-verbal 56.5% and physical 78.3%) or when the shop was crowded (non-verbal 29.3% and physical 88.2%). Most of the victims accepted the problem (non-verbal 55.6% and physical 94.4%) due to fear of being fired and social stigma. Non-verbal (53.8%) and physical (100%) harassments mostly occurred during night shift whereas verbal harassment (63.4%) occurred during day shift. Out of 6 selected predictors: age, dress, place, shift, perpetrator and acceptance of the incident, the verbal harassment was statistically associated with shift (63.6% in day, p-val.= 0.007), non-verbal harassment was associated with age (25% of age 15-30 years, p-val.=0.002) and the physical harassment was statistically associated with age (35% of age 15-30 years, p-val.=0.000), shift (35.0% at night, p-val.=0.000), prepatrators (25% of age 15-30 years, p-val.=0.003), acceptance (40.0% due fear of being fired/ social stigma, p-val.=0.000). In order to reduce sexual harassment among female staffs of supermarkets, there must be awareness programs for all the staff, advocacy programs against SH for customers and staffs, punishment for the perpetrators must be legal.